Review paperBrachytherapy in India – a long road ahead - Banerjee, Susovan; Mahantshetty, Umesh; Shrivastava, Shyamkishore (Journal of Contemporary Brachytherapy, 2014)
Brachytherapy can play a very important role in the definitive cure by radiation therapy in India. However, except for in a handful of centres, the majority of hospitals use it only for intracavitary treatment. The most probable reasons for such are the lack of logistical resources in terms of trained personal and supporting staff, rather than lack of radiotherapy machines and equipment. In this article, the authors look into the various aspects of brachytherapy in India: from its beginning to present days. The authors point out the resources available, shortcomings, and some possible solutions to make use of brachytherapy more popular and effective. Apart from presenting a picture of the present scenario, the article pays attention to the positive signs of brachytherapy becoming more popular in the near future.